2017
DOI: 10.1016/j.indcrop.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Modern extraction techniques optimized to extract betacyanins from Gomphrena globosa L.

Abstract: A B S T R A C TGomphrena globosa L. is a source of betacyanins, molecules with high colorant power. In order to replace conventional extraction techniques, microwave (MAE) and ultrasound assisted extraction (UAE) processes were optimized by the response surface methodology (RSM) to maximize the recovery of betacyanins from G. globosa. A five-level full factorial design of 24 combinations and 4 replicates was implemented for MAE and UAE. The optimum processing conditions for MAE (t = 8 min; T = 60°C; Et = 0%; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 37 publications
2
32
0
2
Order By: Relevance
“…Sivakumar et al () reported that ethanol‐to‐water ratios above 1:1 reduced yield of beetroot dye extract. Roriz et al () reported that for ethanol concentrations in water greater than 20%, extraction of betacyanins is compromised because the compounds' polarities have higher affinities with hydrophilic environments.…”
Section: Resultsmentioning
confidence: 99%
“…Sivakumar et al () reported that ethanol‐to‐water ratios above 1:1 reduced yield of beetroot dye extract. Roriz et al () reported that for ethanol concentrations in water greater than 20%, extraction of betacyanins is compromised because the compounds' polarities have higher affinities with hydrophilic environments.…”
Section: Resultsmentioning
confidence: 99%
“…For betacyanin determination a HPLC-DAD-ESI/MS analysis was performed as previously described by the authors. 16 The detection was carried out with a diode array detector (DAD) using 530 nm as a reference wavelength, and with a Linear Ion Trap LTQ XL mass spectrometer (Thermo Finnigan, San Jose, CA, USA), equipped with an ESI source working in positive mode. The identification was performed by comparing the chromatographic characteristics of available betacyanin standards and using the information available in the literature.…”
Section: Determination Of Phenolic and Betacyanin Compoundsmentioning
confidence: 99%
“…Very recently, PHWE with moderate operation condition has been successively applied in extraction of temperature‐sensitive compounds such as anthocyanins and proteins (Machado, Pasquel‐Reategui, Barbero, & Martinez, ; Salplachta & Hohnova, ). Nonetheless, to the best of our knowledge, there is no report focused on utilization of PHWE in betacyanins extraction from agricultural by‐products even though other innovative techniques, such as microwave‐assisted extraction as well as ultrasound‐assisted extraction (UAE), have been used in colorants recovery from betacyanins‐rich stalks and fruit peels, respectively (Maran & Priya, ; Roriz et al, ).…”
Section: Introductionmentioning
confidence: 99%